Back Cover: Elastic and Wearable Wire‐Shaped Lithium‐Ion Battery with High Electrochemical Performance (Angew. Chem. Int. Ed. 30/2014). Issue 30 (21st July 2014) - Ren, Jing; Zhang, Ye; Bai, Wenyu; Chen, Xuli; Zhang, Zhitao; Fang, Xin; Weng, Wei; Wang, Yonggang; Peng, Huisheng
<x xml:space="preserve">Abstract</x> A safe wire‐shaped lithium‐ion battery consists of two composite yarns, which were prepared from aligned multi‐walled carbon nanotubes and lithium oxides, as the anode and cathode. In their Communication on page 7864 ff., Y. Wang, H. Peng et al. describe that 97 % of the capacity of these lightweight and flexible batteries was retained after 1000 bending cycles. Furthermore, the wire‐shaped batteries were woven into battery textiles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>